A note on characteristic function of sample minimum of order statistics - Demir, Aslihan; Karakas, Ayse Metin; Calik, Sinan (Taylor & Francis Ltd, 2022)
In this study, characteristic function of sample minimum of order statistics are used. The moments of the sample minimum of order statistics from a geometric distribution are achieved by means of characteristic function. Using these moments, the expected value and variance are calculated algebraically and numerically and given in a table.
Keywords: Geometric distribution; Order statistics; Moment; Expected value; Sample minimum; Variance; Characteristic function